Correlation between Yokohama Cytological Coding and Radiological Findings and Their Diagnostic Accuracies against Histopathology: A Retrospective Study of Palpable Breast Lesions - Singh, Puja; Badlani, Bharti; Dehariya, Chanchalesh; Joher, Munira Murtaza (Molecular and Cellular Biomedical Sciences, 2024)
Background: Breast carcinoma is the most common malignancy and demands quick and accurate diagnosis and treatment. Precise diagnosis of breast lesions is made using a triple-test approach: clinical, radiological and cytological. However, multiple steps make the process time-consuming and expensive. In developing countries like India, trained and certified radiologists are extremely overburdened. Fine needle aspiration cytology (FNAC) along with clinical examination can fill the gap. This study aims to correlate cytological, radiological and histological findings and measure their relative accuracies. Based on these findings, a new approach will be proposed to address the above shortcomings.Materials and methods: The FNAC was performed on all cases and reported as per Yokohama cytology. The cytological findings were correlated & validated against radiological and histopathological findings respectively. Relative performance of cytological and radiological findings were established using sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy. A chi-square test for independence between cytological and radiological findings was performed.Results: The sensitivity, specificity, PPV, NPV, and accuracy for cytological findings come out as 97.60, 90.08, 90.37, 97.52, and 93.75, respectively. Meanwhile, the Radiological findings come out as 96.61, 82.20, 84.44, 96.04, and 89.41, respectively. The chi-square test demonstrates strong interdependence between cytological and radiological findings.Conclusion: FNAC is more accurate, quicker, and cheaper than radiological tests. Hence, FNAC based on the Yokohama system, along with clinical observations, can be used as a primary diagnosis tool in developing countries with limited health resources without making significant compromises on incorrect treatment. If needed, radiology and histopathology can be used for precise diagnosis and treatment.Keywords: FNAC, cytology, breast lesions, Yokohama, radiology, histopathology